A Squad with No Left Wingers: The Roots and Structure of Right-Wing and Nationalist Attitudes among Polish Football Fans. Issue 6 (1st November 2020) - Woźniak, Wojciech; Kossakowski, Radosław; Nosal, Przemysław
ABSTRACT: This article examines the lack of political pluralism and the resurgence of nationalism among football fans in Poland. As confirmed by quantitative surveys, Polish fans align with right- or ultra-right wing parties. Left-wing ideology is virtually non-existent at football terraces. The aims of the paper are: to provide a thorough description of Polish fans' political engagement and attitudes; to discuss interrelations between the wider socio-political context and specificity of football fandom and to explain the issue of growing politicization of fandom in the last decade. Finally, several non-mutually exclusive sociological interpretations of the state of affairs are offered.